Bridged-multi-octahedral cobalt oxide nanocrystals with a Co-terminated surface as an oxygen evolution and reduction electrocatalyst. Issue 16 (4th April 2017) - Yiliguma,; Wang, Zhijie; Xu, Wenhao; Wang, Yuhang; Cui, Xiaoqi; Al-Enizi, Abdullah M.; Tang, Yun; Zheng, Gengfeng
Abstract : Cobalt oxide nanocrystals with bridged-multi-octahedral structures and Co-terminated surfaces were prepared to exhibit good oxygen evolution and oxygen reduction performances. Abstract : Cubic cobalt oxide nanocrystals (NCs) with bridged-multi-octahedral structures were prepared by a cooperative mechanism between the particle-based oriented attachment and the atom-mediated crystal growth. The obtained bridged-multi-octahedral NCs show high crystallinity and Co-terminated {111} facets enclosing the octahedrons. Compared to conventional cobalt oxide prepared hydrothermally, this bridged-multi-octahedral NC structure exhibits enhanced electrocatalytic performances towards oxygen evolution and reduction reactions, which is attributed to their preferential exposure of the Co-terminated {111} facets with a low Co coordination number, high electrochemically active surface area, and the reduced charge transfer resistance from the catalytic active sites to the underlying electrode, thus suggesting the tuning of crystal growth for the electrocatalytic enhancement.